Living Alone During Cancer Treatment: An Exploration of Patients' Experiences. (August 2014) - Benoot, Charlotte; Bilsen, Johan; Grypdonck, Maria; Deschepper, Reginald
The social environment is an important determinant in the overall experience of having cancer. The purpose of this article is to identify how patients experience living alone during their cancer treatment. Using qualitative methods based on grounded theory techniques, we interviewed a sample of 32 cancer patients. Living alone was an ambiguous experience during cancer treatment: patients experienced both a lack of support as well a gain in privacy, freedom, and know-how. Living alone was also seen as a constitutive element of the patients' identity. Consequently, patients saw living alone as either a threat or as a resource for their adjustment to cancer treatment. These divergent meanings of living alone did share one common attribute, which was that staying independent was their key goal during cancer treatment. Health care providers should be attentive to the heterogeneous aspects of the experience of living alone when critically appraising the independence of patients.